IDENTIFIKASI MIKROBA POTENSIAL FUNGI MIKORIZA ARBUSKULA (FMA) PADA LAHAN PASCATAMBANG PT. HOLCIM INDONESIA Tbk. CIBINONG, BOGOR, JAWA BARAT - Ceng Asmarahman; Sri Wilarso Budi; Imam Wahyudi; Erdy Santoso (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Impact of mining activity on environment is very significant, especially in the form of pollution on surface water and ground water. Therefore, it is necessary to rehabilitate the damaged ecosystem in post mining land by introduction of arbuscular mycorrhizal fungi (AMF) as source of local potential inoculants. The objective of this research was identifying AMF species on the basis of size, color, and ornament of the spore. Research method comprised identification of species and number of AMF spore in shale post mining location (Site-1) and limestone post mining location (Site-2) with 4 replications for each site. Research result showed the finding of four genera of AMF, namely genera Glomus sp, Scutelospora sp, Gigaspora sp and Acaulosopra sp. Identification result in the first location showed findings of AMF Glomus-1 as many as 186 spores, Glomus-2 as many as 71 spores, Scutelospora as many as 43 spores, Acaulospora as many as 18 spores and Gigaspora as many as 8 spores. On the second site there were identified AMF spores of Glomus-1 as many as 112 spores, Glomus-2 as many as 45 spores, Scutelospora as many as 12 spores and Gigaspora as many as 9 spores. This research is useful for accelerating the success of revegetation in post mining land.